2008
DOI: 10.1523/jneurosci.2666-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Tyrosine Phosphatase STEP Mediates AMPA Receptor Endocytosis after Metabotropic Glutamate Receptor Stimulation

Abstract: Although it is well established that AMPA receptor (AMPAR) trafficking is a central event in several forms of synaptic plasticity, the mechanisms that regulate the surface expression of AMPARs are poorly understood. Previous work has shown that striatal-enriched protein tyrosine phosphatase (STEP) mediates NMDAR endocytosis. This protein tyrosine phosphatase is enriched in the synapses of the striatum, hippocampus, cerebral cortex, and other brain regions. In the present investigation, we have explored whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
270
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(292 citation statements)
references
References 31 publications
14
270
1
Order By: Relevance
“…STEP mediates AMPA and NMDA receptor subunit endocytosis through tyrosine dephosphorylation of their subunits (Zhang et al, 2008;Zhang et al, 2010Zhang et al, , 2011Kurup et al, 2010). In agreement with a recent study (Sun et al, 2013), we found that cocaine reduced the phosphorylation level of the NMDAR subunit GluN2B, an effect prevented by ZM241385 and absent in stA 2A RKO.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…STEP mediates AMPA and NMDA receptor subunit endocytosis through tyrosine dephosphorylation of their subunits (Zhang et al, 2008;Zhang et al, 2010Zhang et al, , 2011Kurup et al, 2010). In agreement with a recent study (Sun et al, 2013), we found that cocaine reduced the phosphorylation level of the NMDAR subunit GluN2B, an effect prevented by ZM241385 and absent in stA 2A RKO.…”
Section: Discussionsupporting
confidence: 93%
“…STEP is highly enriched in the striatum and regulates AMPA receptor internalization (Zhang et al, 2008). The two major isoforms, STEP 46 and STEP 61 , are revealed by western blot analysis in striatal slices, and cocaine (10 mM, 10 min) induced an increase in protein levels of both isoforms ( Figure 4b).…”
Section: Cocaine-induced Synaptic Depression Is Prevented By Ptps Bumentioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, STEP reduces NMDAR activity, negatively regulates LTP, and is required for internalization of both NMDARs and AMPARs from neuronal surfaces (31,32). Based on these results, we hypothesized that STEP may mediate the inhibitory effects of ethanol on NMDAR activity in the brain.…”
Section: Discussionmentioning
confidence: 95%
“…Within striatal regions, Arc protein expression is robustly induced following re-exposure to cocaine-paired stimuli and modulates extinction of drugseeking behavior (Hearing et al, 2011;Hearing et al, 2008). In addition, mGluR activation has been shown to induce rapid translation of striatal-enriched protein tyrosine phosphatase (STEP), which also downregulates AMPAR surface expression and may actively maintain endocytosis rates (Luscher and Huber, 2010;Zhang et al, 2008). Acute exposure to both amphetamine and cocaine alters phosphorylation of STEP in striatal regions and inactivation of STEP prevents cocaineinduced reductions in AMPAR-mediated currents in MSNs (Chiodi et al, 2014;Sun et al, 2007;Tashev et al, 2009;Valjent et al, 2005).…”
Section: Mechanisms Underlying Synaptic Depotentiationmentioning
confidence: 99%